2010
DOI: 10.1590/s1519-566x2010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Nesting behavior of Podium denticulatum Smith (Hymenoptera: Sphecidae)

Abstract: -The nesting behavior of Podium denticulatum Smith was studied on the campus of Ribeirão Preto of the Universidade de São Paulo, SP, Brazil, from September 2003 to August 2005. The wasps established their nests in bamboo canes ranging from 11.4 cm to 26.2 cm in length and from 0.7 cm to 1.8 cm in internal diameter. Podium denticulatum nested almost exclusively in the hot and wet season (September-April), producing at least fi ve generations per year. The cell provisioning was made with adult and nymphal cockro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
12
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 22 publications
9
12
1
7
Order By: Relevance
“…The biology of the Podiini is known from short notes on some species (see Pulawski 2011b) and a few more extensive studies (e.g., Williams 1928, Eberhard 1974, Ribeiro and Garófalo 2010. In the present paper the nesting behaviour of Penepodium luteipenne (Fabricius, 1804) is described, including five alternative nesting tactics and a peculiar female territorial behaviour.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The biology of the Podiini is known from short notes on some species (see Pulawski 2011b) and a few more extensive studies (e.g., Williams 1928, Eberhard 1974, Ribeiro and Garófalo 2010. In the present paper the nesting behaviour of Penepodium luteipenne (Fabricius, 1804) is described, including five alternative nesting tactics and a peculiar female territorial behaviour.…”
Section: Introductionmentioning
confidence: 86%
“…An exception was observed by Ribeiro and Garófalo (2010) who found that P. denticulatum oviposited sometimes before and sometimes after placing its prey in the nest. The behaviour of ovipositing outside the nest may be due to the lack of space inside the nest such that the female cannot assume the characteristic oviposition posture necessary for her to oviposit on a forecoxa of her prey.…”
Section: Oviposition Outside the Nestmentioning
confidence: 97%
See 3 more Smart Citations